The message of Ecological Balance in the Story of Prophet Saleh and Prophet Sulaiman in the Al-Qur’an - Azhari, Hilma Nurlaila; Taufiq, Wildan (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2025)
Environmental damage due to ecological imbalance has become a global issue because of its detrimental impact on all lines of life. One of the main causes is due to the wrong perspective of humans in\ assessing nature. Therefore, the purpose of this study is to determine the meaning of the message of ecological balance in the story of Prophet Saleh and Prophet Sulaiman in the Qur'an using the perspective of literary ecocriticism. The data analysis method used is descriptive-analytical. The result of the research is that ecological balance can be disturbed or maintained accordingly depending on how humans behave. The Thamuds saw nature only as a commodity so they were greedy in using nature, such as making buildings beyond their needs, monopolizing water sources and killing the camel of Prophet Saleh. This attitude then made them damaged the ecological balance and made them destroyed. In contrast to the Prophet Sulaiman who has an attitude of gratitude. So, the Prophet Sulaiman, in utilizing nature, prioritizes fairness and respect. This can be seen from how the Prophet Sulaiman organized the animals that became his army and respected the existence of ants. This attitude then makes the ecological balance maintained and life becomes sustainable.